TRIAD: Whale Optimization Algorithm for 5G-IoT Resource Allocation Decision in Edge Computing - Lieira, Douglas Dias [UNESP] (2021)
The massive growth in the number of 5G-IoT devices circulating in the world has increased the demand for computing resources in recent years. That way, it is necessary to search for the development of new solutions or improvements to existing ones. Edge computing is one of the solutions that have been used to improve the care of these types of devices. In this work, we proposed a mechanism that uses the whale optimization algorithm for 5G-IoT resource allocation decision in edge computing (TRIAD). The TRIAD was compared with the Greedy and Reliable techniques, available in the literature. The results show that the proposed algorithm had excellent efficiency in the service of the devices, in addition to denying fewer requests and blocking fewer devices during the search. The TRIAD, in some situations of the simulation, served approximately 265% more services, denied 56% less requests and blocked 65% less services.